2007
DOI: 10.1007/s11274-007-9479-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a whole cell green fluorescent sensor for lysine quantification

Abstract: As an essential amino acid, lysine is an important component of animal and human diets and its bioavailability can depend on a variety of factors. Therefore, an accurate pre-determination of bioavailable lysine in foods and feeds is important. In this study a whole cell fluorescent biosensor for the quantification of lysine in protein sources was constructed. A gene encoding for green fluorescent protein (GFPmut3) was introduced into an E. coli lysine auxotroph genome as a part of a mini-Tn5-Km transposon. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Oscar [38] also observed that constitutive expression of gfp altered growth characteristics of transformed Salmonella as the changes affected more growth rates and maximum population densities than lag times. In our study, however, L. innocua M1 transformation and gfp expression did not alter the growth rate which agreed with the reports of [39][40][41] for gfp-labeled Bordetella pertussis, Lactococcus lactis and E. coli K-12 strains respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Oscar [38] also observed that constitutive expression of gfp altered growth characteristics of transformed Salmonella as the changes affected more growth rates and maximum population densities than lag times. In our study, however, L. innocua M1 transformation and gfp expression did not alter the growth rate which agreed with the reports of [39][40][41] for gfp-labeled Bordetella pertussis, Lactococcus lactis and E. coli K-12 strains respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, a whole-cell fluorescent biosensor was constructed to quantify lysine in protein sources, which introduced a GFP-encoding gene (GFPmut3) into an E. coli lysine auxotroph genome as a part of a mini-Tn5-Km transposon. (114) Microbial biosensors have also been developed to examine the vitamin content in food products, including vitamin B6, B12, (3) and B1. Recently, a new whole-cell microbial biosensor based on S. cerevisiae was developed to measure vitamin B1 in under 3 minutes and with a detection limit between 0.005 and 0.1 μM.…”
Section: Microbial Biosensors For Food Analysismentioning
confidence: 99%
“…A popular approach is based on tracking promoter activity in response to cell-analyte interactions using endogenously produced reporter molecules (Daunert et al, 2000). Particular analytes of interest include mutagens, heavy metals, phenols, naphthalene, toluene, ammonia, methane, and various biologicals (Chalova et al, 2008;Ron, 2007;Yagi, 2007). Applications that stand to gain from improved whole-cell biosensing technology include air and water quality assessment, bio-warfare defense, drug screening, chemical mutagenicity assessment, and space biology and hazard assessment.…”
Section: Introductionmentioning
confidence: 99%